The Quantum Entanglement Roots of Newton's Gravitational Inverse Square Law via E- Infinity Platonic Transfinite Set Theory (Global Journal of Science Frontier Research, 2020)
Using the E-infinity Cantorian spacetime formalism, i.e. transfinite platonic set theory, we show that Newton's gravitational inverse square law strictly implies quantum entanglement and visa versa to the extent that they are derivable from each other. Noting that the same inverse square law is quasi generic for electrical and magnetic field the unifying role of the Cantorian spacetime of E-infinity becomes evident. The implication and generalization of the above will be explored but its ramifications within physics and beyond is not easily assessed at this early stage of what may amount to a paradigm shift prompted by the simple but very effective golden mean number system, which was suspected recently of being the rationale behind the fine tuning of the universe and the standard model of high energy elementary particle physics.
Keywords: hardy’s quantum entanglement; e-infinity